The Complexity of Ethnic Conflict Among Rohingya Refugees in Aceh: The Struggle Between Local Identity and International Law - Herman Fithra; Muhammad Iqbal; Zulfikar Ali Buto; Mukhlis; Said Alwi (JURNAL PENELITIAN, 2024)
This research examines the complexity of Rohingya refugee integration in Aceh using a qualitative approach and the social religious phenomenology method. The main focus is on the interaction between international law, local norms, religion, mass media, and the social dynamics that influence refugee reception and integration. Data collection methods include in-depth interviews, participatory observation, and document analysis, with informants comprising religious leaders, local government officials, Rohingya refugees, and local journalists. Thematic and narrative analyses are employed to identify and interpret relevant themes related to the application of the non-refoulement principle, the role of Islam, the influence of mass media, and the psychological well-being of refugees. The findings reveal the complexity of Rohingya refugee integration in Aceh, shaped by the interplay of international law, local norms, religion, mass media, and social dynamics. Legal pluralism theory highlights a gap between the non-refoulement principle and Aceh's local wisdom. Religious solidarity theory explains the initial drive for refugee acceptance, though collective historical experiences contribute to resistance. Agenda-setting theory uncovers media bias. The study’s limitations suggest the need for further research, particularly through a comparative approach to understand effective strategies for integrating international law with local norms.